KAJIAN EFISIENSI ALOKASI PENGGUNAAN INPUT PADA USAHA TERNAK AYAM RAS PETELUR - Kustiawati Ningsih (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
The research wasconducted inJune-July 2013 at  Bettet Village Pamekasan City  Subdistrict  Pamekasan  Regency.  The  research  objectivewas  to  determine  the allocation  efficiency  of    input  use  on  breeding  laying  hens.  Secondary  and  primary data  were  obtained  through  interview   and  observation methods.  Descriptive  analysis with  applying  the  Cobb-Douglas  production  function  and  testing  Efficiency  Value Price  for  Input  Use  (Factor)  is  used  to  analyze  the  data.  Results  showed  that  the model  of  Cobb  Douglas  production  function  breeding  laying  hens  at  Bettet  Village Pamekasan City Subdistrict Pamekasan Regenc yis quite good. This can be seen in the value ofR2=0.9585,  meaning that  the independent variable(X1  s/dX6)  in the modelis able to  explain the relationship  with the  dependent  variable  (production) of  95.85%,while  the  remaining  4.15%  is  explained  by  other  variables  not  in  the  study.  In addition,  the results  of the  Cobb  Douglas  production function  model  breeding  laying hens at  Bettet Village have  calculated F value  =  527.485  >  F  table  =  2.599  with =0.05  and  degrees  of  freedom  df(6,20),  meaning  that  the  independent  variables(X1 s/dX6)  together  in  a  model  that  explains  the  relationship  of  the  dependent  variable (production)  significantly.  Assessment  results  for  the  efficiency  of  use  of  each  input prices  (factor)  indicates  that  the allocation of the  inputs  on  breeding  laying hens  at Bettet  Village  Pamekasan  City  Subdistrict  Pamekasan  Regency  still  not  efficient.  It can  be  seen  from  the  t  value  of  each  input  is  greater  thanttable  with  α=0.05and19 degrees of freedom (df =19).